Giant hepatic cavernous hemangiomas : spiral computed tomography findings in 21 patients (2010)
ABSTRACT: Objective: To describe the features of the giant hepatic cavernous hemangioma on spiral CT. Method: During five years, we evaluated 21 patients with 21 giant hepatic cavernous hemangiomas using computed spiral tomography, and 16 and 64 channel multi-slice tomography. The series included 18 women (86%) and 3 men (14%) with a mean age of 45 years. Results: The mean average size of the hemangiomas was 10.4 cm. Non-enhanced computed tomography showed 21 hemangiomas with lower density than the adjacent hepatic parenchyma, all of them containing a low-density central cleft area. No calcifications or internal septations were observed. On the enhanced multi-slice spiral tomography, all lesions demonstrated a globular, peripheral enhancing pattern with centripetal filling beginning in the arterial phase and continuing into the portal and delayed phases. None of the lesions showed complete filling. The degree of enhancement was the same as that of the aorta in all phases. Conclusion: Giant hepatic cavernous hemangiomas show low attenuation on non-enhanced computed tomography. Central cleft areas are seen very frequently. The enhancement pattern is characteristic, starting at the periphery with centripetal filling, but never complete.